Desmoplastic Trichoepithelioma and Melanocytic Nevus: Dermoscopic and Reflectance Confocal Microscopy Presentation of a Rare Collision Tumor - Oliveira, A (2015)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2015-07-09T16:20:07Z No. of bitstreams: 1 JAAD 2015 s13.pdf: 1060789 bytes, checksum: 08814ff9e1c7ad661d138e48a0b170cc (MD5)